Specificity of 3D MSC Spheroids Microenvironment: Impact on MSC Behavior and Properties - Jauković, Aleksandra; Abadjieva, Desislava; Trivanović, Drenka; Stoyanova, Elena; Kostadinova, Milena; Pashova, Shina; Kestendjieva, Snejana; Kukolj, Tamara; Jeseta, Michal; Kistanova, Elena; Mourdjeva, Milena (Stem cell reviews and reports, 2020)
Mesenchymal stem cells (MSC) have been considered the promising candidates for the regenerative and personalized medicine due to their self-renewal potential, multilineage differentiation and immunomodulatory capacity. Although these properties have encouraged profound MSC studies in recent years, the majority of research has been based on standard 2D culture utilization. The opportunity to resemble in vivo characteristics of cells native niche has been provided by implementation of 3D culturing models such as MSC spheroid formation assesed through cells self-assembling. In this review, we address the current literature on physical and biochemical features of 3D MSC spheroid microenvironment and their impact on MSC properties and behaviors. Starting with the reduction in the cells' dimensions and volume due to the changes in adhesion molecules expression and cytoskeletal proteins rearrangement resembling native conditions, through the microenvironment shifts in oxygen, nutrients and metabolites gradients and demands, we focus on distinctive and beneficial features of MSC in spheroids compared to cells cultured in 2D conditions. By summarizing the data for 3D MSC spheroids regarding cell survival, pluripotency, differentiation, immunomodulatory activities and potential to affect tumor cells growth we highlighted advantages and perspectives of MSC spheroids use in regenerative medicine. Further detailed analyses are needed to deepen our understanding of mechanisms responsible for modified MSC behavior in spheroids and to set future directions for MSC clinical application.
Keywords: buněčné mikroprostředí; Cell Survival; buněčné sféroidy; Cell Differentiation; Epigenesis, Genetic; buněčná diferenciace; Mesenchymal Stem Cells; zvířata; Spheroids, Cellular; lidé; Cellular Microenvironment; Humans; epigeneze genetická; viabilita buněk; mezenchymální kmenové buňky; Animals